Effects of childhood trauma on cortisol levels in suicide attempters and ideators - O'Connor, Daryl B.; Green, Jessica A.; Ferguson, Eamonn; O’Carroll, Ronan E.; O'Connor, Rory C. (Elsevier, 2017)
Objectives: Suicide is a global health issue. Dysregulated hypothalamic-pituitary-adrenal (HPA) axis activity, as measured by cortisol levels, has been identified as one potential risk factor for suicide. Recent evidence has indicated that blunted cortisol reactivity to stress is associated with suicidal behavior. The current study investigated whether childhood trauma was associated with blunted cortisol reactivity to a laboratory stressor and resting cortisol levels in suicide attempters and ideators. Methods: 160 participants were recruited and grouped according to history of previous suicidal attempt, suicidal ideation or as control participants. Participants completed background questionnaires, including the Childhood Trauma Questionnaire, before completing a laboratory stress task. Cortisol levels were assessed at rest and during the stress task. Results: The highest levels of childhood trauma were reported in those who had attempted suicide (78.7%), followed by those who thought about suicide (37.7%) and then those with no suicidal history (17.8%). Moreover, regression analyses showed that childhood trauma was a significant predictor of blunted cortisol reactivity to stress and resting cortisol levels, such that higher levels of trauma were associated with lower cortisol levels in those with a suicidal history. Family history of suicide did not interact with the effects of childhood trauma on cortisol levels. Conclusions: These results indicate that childhood trauma is associated with blunted HPA axis activity in vulnerable populations. The challenge for researchers is to elucidate the precise causal mechanisms linking trauma, cortisol and suicide risk and to investigate whether the effects of childhood trauma on cortisol levels are amendable to psychological intervention